INTEGRATING RENEWABLE ENERGY SOLUTIONS IN SUSTAINABLE BUILDING PROJECTS: A CASE STUDY OF NIGERIAN URBAN CENTERS (This article has been retracted due to findings of duplicate publication) - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Jurnal Ilmiah Teknologi dan Rekayasa, 2025)
This study explored the integration of renewable energy solutions in sustainable building projects across three major Nigerian urban centers: Lagos, Abuja, and Port Harcourt. The research focused on the viability and impact of solar photovoltaic (PV) systems, wind energy, and biomass waste-to-energy solutions in reducing energy consumption and greenhouse gas (GHG) emissions. Data were collected through interviews, site visits, and simulations using energy performance modelling software. Advanced data analyses, including cost-benefit analysis (CBA), sensitivity analysis, and life cycle assessment (LCA), were conducted to assess financial viability and environmental impact. The results show that solar PV systems are the most effective, providing energy savings of 25% to 35% with a payback period of 6 to 8 years. Biomass waste-to-energy projects demonstrated promise in industrial settings, while wind energy adoption remains limited due to high upfront costs and longer payback periods. The study identifies key barriers to adoption, such as high initial capital costs, lack of technical expertise, and weak policy enforcement. Policy recommendations include increasing financial incentives, improving policy enforcement, building local technical capacity, and fostering public-private partnerships to accelerate renewable energy adoption in Nigeria’s urban centers.